Predicting the flexural strength of chemically strengthened aluminosilicate glass plates with fractography. Issue 8 (July 2022) - Sun, Huan; Dugnani, Roberto
Abstract: This work introduces a novel, fractographic method to extend the current, state-of-the-art, fractographic techniques to chemically strengthened (CS) glasses with large, surface flaws. The proposed method uses proven relationships based on dimensional analysis to correlate the flexural fracture strength to newly-introduced, fractographic length-scales. The technique requires knowledge of the residual stress profile and access to standard visualization tools such as optical microscopes. The proposed methodology was validated on three sets of aluminosilicate CS glass plates with depth of the compressive layer ( DOL ) ranging between 28 54 μ m and surface stress 980–1140 MPa, and one set of untreated plates. For the CS and untreated glass plates considered, the proposed fractographic technique estimated the fracture strength within (2 ± 11)% of experimental values, which is comparable to the accuracy of fractographic techniques currently used for annealed, brittle specimens.